Long-term prognostic value of late gadolinium enhancement and periprocedural myocardial infarction after uncomplicated revascularization: MASS-V follow-up. (6th December 2020) - Linhares-Filho, Jaime; Hueb, Whady; Lima, Eduardo; Rezende, Paulo; Azevedo, Diogo; Rochitte, Carlos; Nomura, Cesar; Serrano-Junior, Carlos; Ramires, José; Kalil-Filho, Roberto
Abstract: Aims: Cardiac biomarkers elevation is common after revascularization, even in absence of periprocedural myocardial infarction (PMI) detection by imaging methods. Thus, late gadolinium enhancement cardiac magnetic resonance (LGE-CMR) may be useful on PMI diagnosis and prognosis. We sought to evaluate long-term prognostic value of PMI and new LGE after revascularization. Methods and results: Two hundred and two patients with multivessel coronary disease and preserved ventricular function who underwent elective revascularization were included, of whom 136 (67.3%) underwent coronary artery bypass grafting and 66 (32.7%) percutaneous coronary intervention. The median follow-up was 5 years (4.8–5.8 years). Cardiac biomarkers measurement and LGE-CMR were performed before and after procedures. The Society for Cardiovascular Angiography and Interventions definition was used to assess PMI. Primary endpoint was composed of death, infarction, additional revascularization, or cardiac hospitalization. Primary endpoint was observed in 29 (14.3%) patients, of whom 13 (14.9%) had PMI and 16 (13.9%) did not ( P = 0.93). Thirty-six (17.8%) patients had new LGE. Twenty (12.0%) events occurred in patients without new LGE and 9 (25.2%) in patients with it ( P = 0.045). LGE was also associated to increased mortality, with 4 (2.4%) and 4 (11.1%) deaths in subjects without and with it ( P = 0.02). LGE was the only independent predictor of primary endpoint and mortality ( P = 0.03 and P = 0.02). Median LGE mass was estimated at 4.6 g. Patients with new LGE had a greater biomarkers release (median troponin: 8.9 ng/mL vs. 1.8 ng/mL and median creatine kinase-MB: 38.0 ng/mL vs. 12.3 ng/mL; P < 0.001 in both comparisons). Conclusions: New LGE was shown to be better prognostic predictor than biomarker-only PMI definition after uncomplicated revascularization. Furthermore, new LGE was the only independent predictor of cardiovascular events and mortality. Clinical trial registration: http://www.controlled-trials.com/ISRCTN09454308 . Graphical Abstract: